Disappearance of the LO-Phonon line in the Raman spectrum of 6H-SiC - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2000)
We undertook a study of the intensities of optical vibrational modes in the Raman spectrum of 6H-SiC as a function of excitation energy between 2.4 eV and 4.9 eV. A disappearance of the LO0 mode which is the longitudinal optical mode with the highest frequency is observed at 4.38 eV. The result is explained in the framework of a bond-Raman-polarizability model for the Raman scattering cross section as due to the cancellation of the energy dependent bond-Raman polarizabilities of intra- and inter-bilayer bonds that connect the Si and C planes in SiC.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.disapp